2010
DOI: 10.1074/jbc.m109.041517
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Kv1.1 N255D Mutation Associated with Autosomal Dominant Hypomagnesemia

Abstract: Mutations in the voltage, and N255H) did not prevent ion conduction, and these mutant channels activated at more negative potentials when compared with wild-type channels, ؊41.5 ؎ 1.6, ؊45.5 ؎ 2.0, ؊50.5 ؎ 1.9, and ؊33.8 ؎ 1.3 mV to ؊29.4 ؎ 1.1 mV, respectively. The time constant of activation was significantly faster for the two most hydrophobic mutations, N255A (6.2 ؎ 0.2 ms) and N255V (5.2 ؎ 0.3 ms), and the hydrophilic mutant N255T (9.8 ؎ 0.4 ms) in comparison with wild type (13.0 ؎ 0.9 ms). Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…A mutation in KCNA1, encoding Kv1.1, results in a non-functional channel, and has been identified in a family with autosomal dominant hypomagnesaemia. 85,86 Interestingly, other mutations in the same protein cause the neurological syndrome of Episodic Ataxia type 1 -these patients are not reported to be hypomagnesaemic. 87 …”
Section: Kv11 -Autosomal Dominant Hypomagnesaemiamentioning
confidence: 98%
“…A mutation in KCNA1, encoding Kv1.1, results in a non-functional channel, and has been identified in a family with autosomal dominant hypomagnesaemia. 85,86 Interestingly, other mutations in the same protein cause the neurological syndrome of Episodic Ataxia type 1 -these patients are not reported to be hypomagnesaemic. 87 …”
Section: Kv11 -Autosomal Dominant Hypomagnesaemiamentioning
confidence: 98%
“…It is believed that by secreting K 1 , Kv1.1 channels extrude positive charges into the lumen that provide a driving force for TRPM6-dependent Mg 21 transport (Figure 12). Mutation of Kv1.1 at a specific residue renders the channel nonfunctional, and one mutant allele is sufficient to cause the disease, presumably because of dominant negative inhibition of the remaining wild-type allele (117). A current theory is that the lack of functional Kv1.1 channels decreases the efflux of potassium cations into the lumen, which, in turn, would be expected to make the intracellular voltage on the luminal membrane more positive, decreasing the voltage gradient for luminal Mg 21 entry.…”
Section: Magnesiummentioning
confidence: 99%
“…1d). Previously, a homology model was developed (http://www.cmbi.ru.nl/∼hvensela/Kv1.1/, [4]) that was based on the resolved chimaeric Kv1.2-Kv2.1 structure (PDB 2R9R [12]). Figure 1e shows the Kv1.1 homology model and depicts the transmembrane helices surrounding Leu328.…”
Section: Resultsmentioning
confidence: 99%
“…In the DCT, intracellular Mg 2+ levels are comparable to the Mg 2+ concentration in the pro-urine and therefore a chemical gradient for Mg 2+ reabsorption is suggested to be virtually absent. It has therefore been hypothesized that K + secretion via Kv1.1 provides an electrical gradient that drives Mg 2+ reabsorption via TRPM6 [3, 4]. Indeed, our previous studies showed that Kv1.1 activity determined the membrane potential in HEK293 cells [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation